HLA antigens in idiopathic dilated cardiomyopathy. Issue 5 (November 1989) - Limas, C J; Limas, C
Abstract : Disturbances of humoral and cellular immunity are common in patients with idiopathic dilated cardiomyopathy and they may contribute to the initiation and maintenance of myocardial damage. HLA antigens were studied in 102 patients with dilated cardiomyopathy and a control hospital population. HLA-DR4 was significantly more common in patients with idiopathic cardiomyopathy (41 patients, 40%) than in the control group (123 patients, 24%). The distribution of other antigens was not significantly different in the two groups. The distribution of blood group antigens, immunoglobulin concentrations, and disease severity was similar in patients with the HLA-DR4 antigen and those without it. These results suggest that HLA-DR4 antigen may be a genetic marker for susceptibility to dilated cardiomyopathy.